KINERJA KELEMBAGAAN KELOMPOK TANI HUTAN PEMEGANG IZIN PERHUTANAN SOSIAL DI WILAYAH KELOLA KESATUAN PENGELOLAAN HUTAN KAYUTANGI - Istiqomah Istiqomah; Udiansyah Udiansyah; Hamdani Fauzi (Jurnal Sylva Scienteae, 2021)
The objectives of this research was to identified the Forest Farmer Group’s (KTH) Institutional performance as a holder of social forestry permits and to analyze the factors in the Kayutangi Management Unit (KPH). The method used is the sampling snowballs. Snowball sampling is a technique of sampling data sources, which are small in number at first, and over time become large. Analysis of the Institutional Performance of Forest Farmer Group’s (KTH) MPG Suka Maju and the factors that influence the Institutional Forest Farmer Group’s (KTH) MPG Suka Maju. The results of the institutional performance of Forest Farmer Group’s (KTH) MPG Suka Maju as a social forestry permit holder in the Kayutangi Management Unit (KPH) based on the five components of the field (Location Conditions, Institutions, Group Activities, Impact of Group Activities, and Group Achievements). Forest Farmer Group’s (KTH) MPG Suka Maju is categorized as a Forest Farmer Group’s (KTH) quality class "Very Good "With an interval value of 93.69 and factors that affect the institutional capacity of Forest Farmer Group’s (KTH) MPG Suka Maju such as SDM (Human Resources), counseling and assistance to farmer groups are very influential in improving quality institutions.Tujuan dari penelitian ini untuk mengidentifikasi kinerja kelembagaan KTH Pemegang Izin Perhutanan Sosial di Wilayah Kelola KPH Kayutangi dan Menganalisis faktor-faktor yang berpengaruh terhadap kinerja kelembagaan KTH pemegang izin perhutanan sosial di wilayah kelola KPH Kayutangi. Metode yang digunakan yaitu metode Snowball sampling (Pengambilan contoh bola salju). Snowball sampling adalah teknik pengambilan sampel sumber data, yang pada awalnya jumlahnya sedikit, lama-lama menjadi besar. Analisis Kinerja Kelembagaan KTH MPG Suka Maju dan Faktor yang mempengaruhi Kelembagaan KTH MPG Suka Maju. Hasil Kinerja kelembagaan KTH MPG Suka Maju sebagai pemegang izin perhutanan sosial di Wilayah kelola KPH Kayutangi berdasarkan komponen kelima bidang (Kondisi Lokasi, Kelembagaan, Aktifitas Kelompok, Dampak Kegiatan Kelompok, dan Prestasi Kelompok) KTH MPG Suka Maju ini dikategorikan sebagai kelas kualitas KTH “Sangat Bagus” dengan nilai interval 93.69 dan Faktor-faktor yang berpengaruh terhadap kapasitas kelembagaan KTH MPG Suka Maju seperti SDM (Sumber Daya Manusia), Penyuluhan dan Bantuan terhadap kelompok tani sangat berpengaruh dalam meningkatkan kelembagaan yang berkualitas.